Just push play! - Expressividade e idiomática de instrumentos musicais digitais - Lopes Rocha, Gabriel (2022)
The creation of a digital musical instrument is an activity that has attracted musicians and researchers for decades and certainly has open problems on which these researches have focused. Indeed, creating an instrument can be a simple task that consists of organizing an interface so that it serves to make sound. However, this simple interface may be far from what we consider a musical instrument when we think that generating sound may not be the only thing we are looking for when playing an instrument.